2014
DOI: 10.1371/journal.pone.0085787
|View full text |Cite
|
Sign up to set email alerts
|

Detrended Fluctuation Analysis and Adaptive Fractal Analysis of Stride Time Data in Parkinson's Disease: Stitching Together Short Gait Trials

Abstract: Variability indicates motor control disturbances and is suitable to identify gait pathologies. It can be quantified by linear parameters (amplitude estimators) and more sophisticated nonlinear methods (structural information). Detrended Fluctuation Analysis (DFA) is one method to measure structural information, e.g., from stride time series. Recently, an improved method, Adaptive Fractal Analysis (AFA), has been proposed. This method has not been applied to gait data before. Fractal scaling methods (FS) requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 58 publications
2
45
0
Order By: Relevance
“…Differences in the short-range statistical correlations detected in these relatively short recordings may be sufficient to characterize differences in gait dynamics between two groups or experimental conditions as shown by Kirchner et al [16]. The question we sought to answer was how many subjects and trials are required when researchers are limited to collecting only 100–200 strides per trial (this corresponds to 2 to 4 minutes of walking assuming stride time of 1.2 s).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the short-range statistical correlations detected in these relatively short recordings may be sufficient to characterize differences in gait dynamics between two groups or experimental conditions as shown by Kirchner et al [16]. The question we sought to answer was how many subjects and trials are required when researchers are limited to collecting only 100–200 strides per trial (this corresponds to 2 to 4 minutes of walking assuming stride time of 1.2 s).…”
Section: Introductionmentioning
confidence: 99%
“…We attempted to overcome this by removing all segments shorter than 5 minutes. We also compared our preprocessing approach to estimate α from all segments with an alternative approach 42 and found that they were statistically equivalent (data not shown).…”
mentioning
confidence: 99%
“…Several different methods have been developed in the past years to detect fractal and multifractal signatures. Among the many we can cite multifractal detrended fluctuation analysis (MF-DFA) [18], adaptive fractal analysis [22], wavelet transform modulo maxima [28], and wavelet leaders [23]. Fractal and multifractal analysis of time series play a pivotal role in many scientific contexts, such as neuroscience and medicine in general [9,10,37].…”
mentioning
confidence: 99%